Una tentación cosmopolita - Schlesinger, Philip (CIC. Cuadernos de Información y Comunicación, 2009)
For some, the transnationalization of political action and communicative space in the European Union heralds an emergent cosmopolitan order. Need that be so? There are supranational institutions in the EU as well as transnationa political and cultural spaces and cross-border communicative flows.However, the Union’s member states remain key controllers of citizenship rights and purveyors of collective identities. And for many purposes they still maintain strongly bounded national public spheres. Because the EU’s overall character as a polity remains unresolved, this has consequences for the organization of communicative spaces. The EU is a field of tensions and contradictions that is inescapably rooted in institutional realities. Wishfulthinking about cosmopolitanism can get in the way of clear analysis.
Keywords: Collective identity; Cosmopolitanism; European Union; Nation; Public sphere; State